Use Of Google Earth To Facilitate GIS-Based Decision Support Systems For Arthropod-Borne Diseases - Lozano Fuentes, Saúl; Elizondo Quiroga, Darwin; Farfán Ale, José Arturo; Fernández Salas, Ildefonso; Beaty, Barry J.; Eisen, Lars (International Society for Disease Surveillance, 2007)
As part of a Dengue Decision Support System project funded by the Innovative Vector Control Consortium, we used satellite imagery and mapping tools freely available through Google Earth to: 1) generate data for basic city structure that could be imported into a Geographic Information System (GIS); and 2) serve as the spatial underpinning of a Decision Support System for arthropod-borne disease management.